-8x(8x-8)=0

Simple and best practice solution for -8x(8x-8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x(8x-8)=0 equation:



-8x(8x-8)=0
We multiply parentheses
-64x^2+64x=0
a = -64; b = 64; c = 0;
Δ = b2-4ac
Δ = 642-4·(-64)·0
Δ = 4096
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{4096}=64$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(64)-64}{2*-64}=\frac{-128}{-128} =1 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(64)+64}{2*-64}=\frac{0}{-128} =0 $

See similar equations:

| (x+64)=90 | | (X)^2+x=99 | | 1-8x=3-10x | | (x+69)=90 | | (x+69)=180 | | 4x–1=29 | | 2(x-7)-8(x-4)=-7x+11 | | 4=2x−7 | | 7x+5=2-9x | | (6x+12)=90 | | -4r(r+6)=-57 | | (x-3)-(-4x+7)=5 | | 7/x=91 | | -4(5x-3)=112 | | 5m-3=18-2m | | 5x–14=6 | | 4x*2+25x=0 | | 18-4x=28+6x | | 3x−2= | | 3x−2=x | | k-1=k-5 | | -3(4x+1)-(2x+3)=0 | | 4c-40=-14c+14 | | 3(2x-4)=(12-x) | | 35g-29=14-8g | | 4(3x+6)=-24 | | 4x+43+2x-12=9x-26 | | 2x-15=7x-45 | | x-(3+2)=5 | | -30=5(x+1)−30 | | 2(x-10)-19(x-13)=-18x+3 | | 8=-2k-7+5k |

Equations solver categories